2013
DOI: 10.1002/jib.72
|View full text |Cite
|
Sign up to set email alerts
|

Production of alcohol-free beer with elevated amounts of flavouring compounds using lager yeast mutants

Abstract: Arrested or limited fermentation process is a widespread method used for production of alcohol-free beer (AFB). However, it usually leads to worty off-flavour and a lack of pleasant fruity flavour/aroma. The aim of this study was to isolate spontaneous mutants of Saccharomyces pastorianus strain 2 resistant to 5,5,5-trifluoro-DL-leucine, since the resistance is related to overproduction of flavour active isoamyl alcohol (IAAL) and isoamyl acetate (IAAC). The mutants were the subject of selection during series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 25 publications
2
40
0
Order By: Relevance
“…A number of investigations have demonstrated the feasibility of directing evolution in natural Saccharomyces pastorianus hybrid stains in order to create variant strains with improved functional properties [6]. Such investigations have focused on adaptation to very high-gravity brewing conditions [7][8][9], associated stresses (such as osmotic stress and ethanol toxicity) [10,11], or the modification of the production of flavour compounds [12]. ALE has also been utilised to enhance the fermentation rate of S. cerevisiae with decreased formation of acetate and greater production of aroma compounds [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…A number of investigations have demonstrated the feasibility of directing evolution in natural Saccharomyces pastorianus hybrid stains in order to create variant strains with improved functional properties [6]. Such investigations have focused on adaptation to very high-gravity brewing conditions [7][8][9], associated stresses (such as osmotic stress and ethanol toxicity) [10,11], or the modification of the production of flavour compounds [12]. ALE has also been utilised to enhance the fermentation rate of S. cerevisiae with decreased formation of acetate and greater production of aroma compounds [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…High losses of volatile compounds have been reported during the lab-scale vacuum dealcoholization process and also when commercial regular beers and their related nonalcoholic beers were compared (Zürcher et al 2005;Montanari et al 2009;Lehnert et al 2009;Brányik et al 2012;Strejc et al 2013). In this study, the major losses were found over the initial period of the dealcoholization experiments, and, hence, although the system is only nearly comparable to the industrial scale ones, our results suggest that the volatile compound behavior is likely to be also comparable.…”
Section: Discussionmentioning
confidence: 97%
“…There are a number of examples of this approach, leading to the design of S. pastorianus (123,124) or S. cerevisiae strains (125) with enhanced performances. Examples also include the design of S. pastorianus strains for improved growth under hyperosmotic conditions (126) or with improved production of flavor compounds (127,128). Finally, a possible solution to overcome consumer distaste towards GMO could be the application of self-cloning yeasts because only homolog DNA or DNA from a closely related organism are inserted or modified (135).…”
Section: Designing Superior Yeastsmentioning
confidence: 98%